2004
DOI: 10.1109/tgrs.2004.836792
|View full text |Cite
|
Sign up to set email alerts
|

Ground-based radar interferometry for landslides monitoring: atmospheric and instrumental decorrelation sources on experimental data

Abstract: The application of ground-based radar interferometry for landslide monitoring is here analyzed: a case study based on an experimental campaign carried out in Italy in the year 2002 is discussed. Interferometric data obtained from coherent synthetic aperture radar (SAR) images acquired by means of C-band ground-based equipment are analyzed. The campaign was aimed at retrieving potential terrain movements of a small landslide observed hundreds of meters away. Critical aspects related to spatial and temporal dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(79 citation statements)
references
References 21 publications
0
78
0
1
Order By: Relevance
“…The first study of the APS in GB-SAR applications (Luzi et al 2004) found an empirical linear relationship between φ atm and range. Some studies applied polynomial (Noferini et al 2005) or multilinear regressions (Iglesias et al 2014;Caduff et al 2014) to the phase observed in areas assumed to be stable, where Φ int ' φ atm , to estimate spatial maps of the APS.…”
Section: Methodsmentioning
confidence: 99%
“…The first study of the APS in GB-SAR applications (Luzi et al 2004) found an empirical linear relationship between φ atm and range. Some studies applied polynomial (Noferini et al 2005) or multilinear regressions (Iglesias et al 2014;Caduff et al 2014) to the phase observed in areas assumed to be stable, where Φ int ' φ atm , to estimate spatial maps of the APS.…”
Section: Methodsmentioning
confidence: 99%
“…A SAR image is obtained by combining the spatial resolution along the direction perpendicular to the rail (range resolution, ΔRr), and that parallel to the synthetic aperture (azimuth or cross-range resolution, ΔRaz) (Luzi 2010). This image contains amplitude and phase information, measured during the acquiring time interval, regarding the backscattered echo of the observed scenario (Luzi et al 2004;Monserrat et al 2014). The working principle of the GB-InSAR technique is the evaluation of the phase difference, pixel by pixel, between two pairs of averaged sequential SAR complex images, which constitutes an interferogram (Bamler and Hartl 1998).…”
Section: Gb-insar Theoretical Principlesmentioning
confidence: 99%
“…In the last two decades, amongst the many new methods used in landslide investigation, terrestrial-based technologies such as digital photogrammetry (Zhang et al 2004;Sturzenegger and Stead 2009), light detection and ranging (LiDAR; Oppikofer et al 2009;Fanti et al 2013), infrared thermography (Gigli et al 2014a, b;Frodella et al 2015), and groundbased radar interferometry (GB-InSAR) (Luzi et al 2004;Lombardi et al 2016) are increasingly being recognized as efficient remote surveying techniques for the characterization and monitoring of landslide-affected areas, in terms of resolution, accuracy, data visualization, management and reproducibility. GB-InSAR systems in particular, for their capability of measuring displacements with high geometric accuracy, temporal sampling frequency and adaptability to specific applications (Monserrat et al 2014), represent powerful devices successfully employed in engineering and geological applications for detecting structural deformation and surface ground displacements (Tarchi et al 2003;Antonello et al 2004;Casagli et al 2010Casagli et al , 2017, for the monitoring of volcanic activity (Di Traglia et al 2014a, b), and for analysing the stability of historical towns built on hilltops (Luzi et al 2004;Nolesini et al 2016). In recent years, GB-InSAR technique has developed to an extent where it can significantly contribute to the management of major technical and environmental disasters (Broussolle et al 2014;Frodella et al 2016;Bardi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The working principle of the GB-InSAR technique involves radiating microwaves toward the investigated area and measuring the backscattered signal, obtaining a SAR image. The SAR image is created by combining the spatial resolution along the direction perpendicular to the rail (range resolution; ΔRr) and the one parallel to the synthetic aperture (azimuth, or cross-range resolution; ΔRaz) (Luzi 2010), containing amplitude and phase information of the backscattered echo from the investigated scenario objects.…”
Section: Gb-insar Monitoringmentioning
confidence: 99%